2020
DOI: 10.12968/hmed.2019.0371
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette or vaping product use-associated lung injury

Abstract: E-cigarette or vaping product use-associated lung injury is a recently recognised, acute pulmonary syndrome which has been reported (particularly from June to October 2019) throughout the USA, but not in Europe (although one probable case, in the UK, has been reported; Medicines and Healthcare products Regulatory Agency, 2020 ). It presents acutely, most often in young men, as severe pulmonary consolidation, usually with respiratory failure. The mortality is around 2%. The cause(s) are unknown, but it is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
12
0
5
Order By: Relevance
“…The lack of a significant finding between educational level and knowledge and perceptions of the dangers of vaping suggests that all adults need sound education regarding the dangers of vaping, irrespective of their educational backgrounds. The incidence of EVALI has increased and patients, with this acute condition acutely most often present with severe pulmonary consolidation with respiratory failure [ 1 ]. Based on our participants’ responses, we found that if the dangers of vaping were discussed with them by their health care providers, they would be more inclined to quit vaping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a significant finding between educational level and knowledge and perceptions of the dangers of vaping suggests that all adults need sound education regarding the dangers of vaping, irrespective of their educational backgrounds. The incidence of EVALI has increased and patients, with this acute condition acutely most often present with severe pulmonary consolidation with respiratory failure [ 1 ]. Based on our participants’ responses, we found that if the dangers of vaping were discussed with them by their health care providers, they would be more inclined to quit vaping.…”
Section: Discussionmentioning
confidence: 99%
“…Vaping is inhaling smoke from electronic cigarettes (e-cigarettes) that may contain nicotine, tetrahydrocannabinol, and cannabidiol [ 1 ]. Vaping is now recognized as a global public health crisis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis is further supported by his initial presentation of gastrointestinal symptoms preceding the ARDS. EVALI patients are more susceptible to clinical deterioration; 50% of the patients will require admission to the Intensive care unit, 20% will require intubation and mechanical ventilation, and the mortality rate is 2% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of vaping devices from first generation of cig-a-like products to the sophisticated fourth generation devices underline the popularity and commercial success of this highly addictive and dangerous strategy. The global e-cigarettes (vaping) market was valued at about $14.05 billion in 2018 and is expected to more than double through 2022 [3] .…”
Section: Introductionmentioning
confidence: 99%